Integrating Ethno-Ecological and Scientific Knowledge of Termites for Sustainable Termite Management and Human Welfare in Africa - Sileshi, Gudeta W.; Nyeko, Philip; Nkunika, Phillip O. Y.; Sekematte, Benjamin M.; Akinnifesi, Festus K.; Ajayi, Oluyede C. (Ecology and Society, 2009)
Despite their well-known role as pests, termites also provide essential ecosystem services.In this paper, we undertook a comprehensive review of studies on human–termite interactions and farmers’ indigenous knowledge across Sub-Saharan Africa in an effort to build coherent principles for termite management. The review revealed that local communities have comprehensive indigenous knowledge of termite ecology and taxonomy, and apply various indigenous control practices. Many communities also have elaborate knowledge of the nutritional and medicinal value of termites and mushrooms associated with termite nests. Children and women also widely consume termite mound soil for nutritional or other benefits encouraged by indigenous belief systems. In addition, subsistence farmers use termites as indicators of soil fertility, and use termite mound soil in low-risk farming strategies for crop production. In the past, chemical control of termites has been initiated without empirical data on the termite species, their damage threshold, and the social, ecological, or economic risks and trade-offs of the control. This review has provided new insights into the intimate nature of human–termite interactions in Africa and the risks of chemical control of termites to human welfare and the environment. We recommend that management of termites in future should be built on farmers’ indigenous knowledge and adequate understanding of the ecology of the local termite species.
Keywords: Agroforestry; biodiversity; geophagy; management; traditional ecological knowledge